Parallel discrete event simulation on desktop grid computing infrastructures. (22nd September 2009) - Park, Alfred; Fujimoto, Richard M.
In contrast to traditional Parallel Discrete Event Simulation (PDES) systems using dedicated machines, an alternative master/worker approach for high throughput execution on shared computing platforms is proposed. Master/worker systems offer potential advantages over traditional PDES systems such as better support for heterogeneous machines, client-driven load balancing, fault tolerance, and execution on non-dedicated machines. We examine feasibility of executing PDES codes on master/worker systems. We characterise application properties that are important for efficient execution and define suitable performance metrics. The Aurora Parallel and Distributed Simulation System utilising the master/worker approach is described along with performance measurements in executing conservative PDES codes.